Lessons From Insect Fungiculture: From Microbial Ecology to Plastics Degradation - Barcoto, Mariana O.; Rodrigues, Andre (Frontiers in Microbiology, 2022)
Anthropogenic activities have extensively transformed the biosphere by extracting and disposing of resources, crossing boundaries of planetary threat while causing a global crisis of waste overload. Agroindustrial bio-waste and xenobiotic pollutants are considered potential sources of energy and value-added products that could be explored through the wide metabolic diversity of microorganisms. Lignocellulolytic microbial communities are of special interest when prospecting for efficient microbial degraders or modifiers of recalcitrant materials since lignocellulose components and xenobiotic pollutants have chemical and structural similarities. An intriguingly efficient lignocellulolytic microbial community is found in fungus-growing insects (FGI), comprising the attine ants, macrotermitine termites, and ambrosia beetles. Insect farmers cultivate lignocellulolytic fungi that rely on a wide biochemical arsenal to convert recalcitrant plant polymers into nutrient-rich food, accessed by the insect via mycophagy. The characteristic and seemingly adapted FGI microbiota has the potential to integrate metabolic pathways for lignocellulose depolymerization. Here, we review the literature to provide a perspective on how the FGI lignocellulolytic arsenal could inspire biotechnological innovations aiming at biofuel production and bioremediation of xenobiotics (as plastics and chemical pollutants). We suggest multidisciplinary strategies to take advantage of metabolic pathways important for FGI ecological success. Spanning from multiomics to spectroscopy, microscopy, stable isotopes probing, enrichment microcosmos, and synthetic communities, these strategies would allow for a systemic understanding of the FGI microbiota potential and application possibilities. As insect-associated microbial consortia have inspired biomimetic approaches towards a circular economy, the FGI microbiota could integrate sustainable efforts for mitigating the current environmental crisis.